2017
DOI: 10.1039/c7cc00765e
|View full text |Cite
|
Sign up to set email alerts
|

Boronic acid-modified alginate enables direct formation of injectable, self-healing and multistimuli-responsive hydrogels

Abstract: Abstract. One-step functionalization of alginate with boronic acid groups allowed spontaneous formation of biocompatible hydrogels under basic conditions without additional complementary molecules or crosslinking agents. The dynamic nature of boronate ester bonds formed with vicinal diols present on alginate pyranose rings provided remarkable self-healing, injectable and multi-stimuli responsive properties to the material.Stimuli-responsive hydrogels are characterized by the ability to respond to external trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
121
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(121 citation statements)
references
References 25 publications
0
121
0
Order By: Relevance
“…Next, we sought to study the gels as cell encapsulants, as several studies have shown that soft hydrogels can support the retention of viable cells within polymeric matrices for cell delivery/therapy and tissue engineering applications. 60,69,72,102,[108][109][110] Optical microscopy images showed that H9c2 cells could spread evenly within the gel matrix, retained their morphology and apparently increased their density when cultured for 48 hours (Fig. 8b and c); also, the cells predominantly remained alive throughout the culture period as evidenced by the intense green fluorescent signal ( Fig.…”
Section: Self-healing Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we sought to study the gels as cell encapsulants, as several studies have shown that soft hydrogels can support the retention of viable cells within polymeric matrices for cell delivery/therapy and tissue engineering applications. 60,69,72,102,[108][109][110] Optical microscopy images showed that H9c2 cells could spread evenly within the gel matrix, retained their morphology and apparently increased their density when cultured for 48 hours (Fig. 8b and c); also, the cells predominantly remained alive throughout the culture period as evidenced by the intense green fluorescent signal ( Fig.…”
Section: Self-healing Propertiesmentioning
confidence: 99%
“…Finally, we demonstrate that these materials can be used as bulk cell encapsulants for cell delivery applications aimed to soft tissue engineering applications, [69][70][71][72] owing to the mild mixing and recovery conditions for their preparation and reconstruction. Such functionalities in terms of multi-responsiveness and healability, combined with excellent cytocompatible properties, have not been extensively exploited in previous boronic acid-based studies, 33,60,64,73 and hence, we anticipate that our study will be inspirational towards the development of functionally more complex, yet synthetically accessible, materials for the biomedical field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pettignano et al. reported injectable, self‐healable, and multistimuli‐responsive hydrogels consisting of alginate modified with PBA moieties . Reversible bonds between the boronate and diol of the alginate enabled the gel to form under basic conditions, be responsive to pH and competitive sugar, exhibit self‐healing after cutting, and have high cell viability inside the gel.…”
Section: Other Functional Systemsmentioning
confidence: 99%
“…[17,21,22] Ferrocene-functionalised hydrogel can change its hydrophilicity and hydrophobicity by changing the oxidation state of the Fe centre. Boronate ester mediated LMW G4 hydrogels are dynamic, self-healablea nd thixotropic in nature owing to the dynamic behaviour of the boronic acid-boronate ester equilibrium in aqueous medium.…”
Section: Introductionmentioning
confidence: 99%